(untitled) (Ukrainian Journal of Ophthalmology, 2023)
Background: Phacoemulsification (phaco) of mature intumescent cataract is one of the most difficult to perform anterior eye surgeries. In mature intumescent cataract phaco, the most difficult phase is performing a continuous capsulorhexis which should be as round as possible. The incidence of an anterior capsular tear during capsulorhexis has been reported to range from 0.8 to 5.0% and increases with an increase in cataract density. This is because in dense intumescent cataracts, capsulorhexis tends to extend to the periphery due to high intracapsular pressure. Femtosecond laser–assisted phaco of mature intumescent cataract enables a safe laser-assisted capsulotomy with a substantially reduced risk of intraoperative complications. Because this approach is as yet not widely used in ophthalmology, we aimed to share our experience in the use of femtosecond laser in phacoemulsification of mature and intumescent cataracts. Purpose: To assess the efficacy of femtosecond laser–assisted treatment of mature intumescent cataract. Methods: Sixty-five patients (68 eyes) with mature intumescent senile cataract underwent femtosecond laser-assisted cataract surgery (FLACS) with intraocular lens (IOL) implantation and were involved in this study. Results: In 55 eyes (80.8%), laser capsulotomy of the desired diameter (5.0 mm) was performed completely. In 8 eyes (11.7%), capsular bridges (capsular tissue remnants at the site of laser-assisted cut of the anterior capsule) were seen. In addition, after the laser phase of surgery, 3 eyes (4.4%) showed an irregularly shaped anterior capsular disc due to the failure of the laser to cut through the capsule in several regions. In all study eyes, the IOL was well centered in the bag. Conclusion: In eyes with mature intumescent cataract, it is reasonable to use the femtosecond laser for a safe and accurate anterior capsulorhexis to avoid the severe intraoperative complications (those associated with posterior capsular rapture and vitreous prolapse) that can be seen during manual capsulorhexis.